Pengaruh Brand Image dan Persepsi Kualitas terhadap Minat Beli Iphone di Surabaya - Abdu Fitrah Indarto; Siti Ning Farida (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Competition in running an economy is experiencing a rapid increase, not least in the competition in the world of technology. Various kinds of companies in the world are currently fighting for the interest of the consumer market. The purpose of this research is to determine the impact of brand image and perceived quality variables on buying interest in iPhone products in the city of Surabaya. The research method is to use a quantitative approach. The research conducted by the researcher refers to the use and measurement of the linkert scale which is calculated from 1 to 5. The number of samples used is 100 samples. The data analysis test used in this study refers to the multiple linear regression test. Quality Perception Variable (X2) has a significant effect on buying interest (Y) Iphone in Surabaya. Subsequent test results have also shown . Variables of perceived quality (X2) and perceived quality (X2) together have a significant effect on buying interest (Y). Keywords: Brand image, Perceived quality and Purchasing Intetion